Determinan Perilaku Pencegahan COVID-19 Pasca Pandemi pada Pengunjung Rumah Sakit “X” di Jakarta tahun 2023 - Mariyono Soepadji; Susiana Nugraha; Yeny Sulistyowati (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
Hospital visitors are at high risk of being exposed to and infected by infectious diseases. Data on visitors to Hospital "X" in Jakarta was obtained on an average of 7,700 people per month. The aim of this research is to analyze the relationship between knowledge, attitudes and availability of infrastructure and post-pandemic COVID-19 prevention behavior among visitors to hospital "X". This research is a correlational study with a cross-sectional approach, carried out in May - August 2023 at "X" Hospital Jakarta, using 119 respondents. The Probability Sampling sampling method uses the Slovin formula. The variables studied are knowledge, attitudes, infrastructure and behavior. The research instrument is a questionnaire. Data was obtained through an online questionnaire using Google Form. The data obtained was then analyzed univariately, bivariately and multivariately. The Chi-Square test results showed a significant relationship between knowledge and post-pandemic COVID-19 prevention behavior (p-value=0.005); there is a significant relationship between attitudes and COVID-19 prevention behavior throughout the pandemic (p-value=0.001); There is a significant relationship between infrastructure and post-pandemic COVID-19 prevention behavior (p-value=0.024). Attitude is the dominant factor in influencing post-pandemic COVID-19 prevention behavior (OR=5.410). Knowledge, attitudes and infrastructure are variables that influence post-pandemic COVID-19 prevention behavior among visitors to Hospital "X" in Jakarta, so efforts need to be made to increase knowledge, attitudes through socialization, health education and enforcement of infectious disease prevention rules, as well as providing infrastructure in each health facility.